Ge 기반 소자의 열안정성 향상을 위한 ZrO2/Ge 페시베이션 층의 효과 연구 - 원병준 (The Graduate School, Ajou University, 2024)
This paper analyzes the characteristics of Al2O3 and Y2O3 passivation layers applied to Ge substrates using atomic layer deposition (ALD) to enhance the thermal stability of Ge-based devices. As device scaling and improvements through channel materials continue to be researched for semiconductor performance enhancement, Ge, with its superior mobility, is gaining attention as a potential replacement for Si. However, native GeOx formed in Ge exhibits unstable interface properties and volatilizes at high temperatures, which degrades device performance. To address these issues, passivation research has been conducted using various high-k materials (Al2O3, Y2O3, HfO2, CeO2, La2O3, etc.). This study focuses on analyzing the effects of Al2O3, which possesses high bandgap energy properties, and Y2O3, a rare earth material with excellent interface properties, as passivation layers. Particularly, it compares interface characteristics by effectively controlling unstable GeOx and analyzes the chemical and electrical properties of Ge-based devices in high-temperature environments. Thus, this research aims to contribute to the performance improvement of next-generation semiconductor devices by elucidating the impact of thermal stability enhancement in Ge-based devices.|이 논문에서는 Ge 기반 소자의 열 안정성을 향상시키기 위해 Ge 기판에 원자층 증착 (ALD)를 기반으로 Al2O3 및 Y2O3 패시베이션 층의 적용에 따른 특성을 분석했다. 반도체 의 성능 향상을 위해 소자 스케일링과 더불어 채널물질을 통한 특성개선이 연구되는 가운 데, Si을 대체할 수 있는 Ge은 우수한 이동도로 각광받고 있다. 그러나 Ge에서 생성되는 native GeOx는 불안정한 계면특성 및 고온에서 휘발성으로 소자 특성이 저하되는 문제점 이 있다. 이러한 특성을 개선하기 위한 목적으로 다양한 High-k 물질(Al2O3, Y2O3, HfO2, CeO2, La2O3 등)을 응용한 패시베이션 연구가 진행되어왔다. 본연구에서는 이중 높은 밴 드갭 에너지의 특성을 지닌 Al2O3와 희토류 물질로서 우수한 계면특성을 가지는 Y2O3의 패시베이션 층으로서의 효과를 분석한다. 특히, 불안정한 GeOx을 효과적으로 제어함에 따 른 계면 특성을 비교 분석하고, 이를 통해 고온 환경에서의 Ge기반 소자의 화학적 특성, 전기적 특성을 통해 분석한다. 따라서, Ge 기반 소자의 열 안정성 개선에 미치는 영향을 밝혀 차세대 반도체 소자의 성능 개선에 기여할 수 있는 연구를 제시하고자 한다. 주제어 : Atomic Layer Deposition, Ge Device, Passivation Layer, Thermal Stability, Channel Materials
학위논문(석사)--지능형반도체공학과,2024. 8
Keywords: Atomic layer deposition; Ge diffusion; Ge passivation effect of Al2O3; Ge passivation effect of Y2O3; Ge-based devices; Germanium oxide; Interlayer; Thermal stability; ZrO2/Ge interface